Enhanced mechanical and thermal properties of ionic liquid core/silica shell microcapsules-filled epoxy microcomposites. (26th October 2021) - Shi, Ting; Livi, Sébastien; Duchet-Rumeau, Jannick; Gérard, Jean-François
Abstract: A new type of phosphonium ionic liquid (trihexyl (tetradecyl) phosphonium bis(2, 4, 4-trimethylpentyl) phosphinate core/silica shell microcapsules (IL@SiO2 ) was successfully synthesized by one pot sol-gel process in IL/H2 O emulsion and combined to epoxy amine networks as reinforcing fillers. Different amounts of IL@SiO2 microcapsules and epoxy-to- amine stoichiometric ratios were considered in order to investigate the mechanical and thermal properties of IL@SiO2 filled epoxy composites. It has been found that IL@SiO2 could be easily well dispersed in the epoxy matrix and low amounts of microcapsules can improve modulus and fracture toughness of epoxy-IL@SiO2 composites without damaging thermal properties. This reinforcement effect could be also observed when the epoxy-to-aminohydrogen ratio is over 1.0. This study is a preliminary work combining these new microcapsules with thermosetting polymers and give inspirations for the design of functional new epoxy-based materials. Graphical abstract: Image 1 Highlights: Design of novel ionic liquid core/silica shell microcapsules by one pot sol-gel process. Excellent distribution of the microcapsules (0.6–1 μm) into epoxy-amine network. Improvement of the mechanical properties, especially fracture toughness of the epoxy networks.